Voici quelques équations :
a) 4x+3=3x - 5 ;
b) -2x+7 = 3x-13
c) -3x+4=6x+5
d) 4-7x= -3x+1
e) 3 (x-8)=4x+5
f) -4(2+x) = 3x-5
g) 9(2-2x)= - (7x+1)
h) -3 (4+x) + 3x = 6(x+1)
i) 2(-5x+3) + 7(3x-1)=0
j) 5(4x+3) + 2(x+6) = 3(x+8)

2

Réponses

2014-03-31T18:37:19+02:00
H) -3 (4+x) + 3x = 6(x+1) 
i) 2(-5x+3) + 7(3x-1)=0
j) 5(4x+3) + 2(x+6) = 3(x+8)a) 4x+3=3x - 5 
4x-3x=-5-3
x=-8

b) -2x+7 = 3x-13
-2x-3x=-13-7
-5x=-20
x=-20/-5
x=4

c) -3x+4=6x+5
-3x-6x=5-4
-9x=1
x=1/-9
x=-1/9

d) 4-7x= -3x+1 
-7x+3x=1-4
-4x=-3
x=-3/-4
x=3/4

e) 3 (x-8)=4x+5
3*x+3*(-8)=4x+5
3x-24=4x+5
3x-4x=5+24
-x=29
x=-29

f) -4(2+x) = 3x-5
-4*2-4*x=3x-5
-8-4x=3x-5
-4x-3x=-5+8
-7x=3
x=3/-7
x=-3/7

g) 9(2-2x)= - (7x+1)
9*2+9*(-2x)=-7x-1
18-18x=-7x-1
-18x+7x=-1-18
-11x=-19
x=-19/-11
x=19/11

h) -3 (4+x) + 3x = 6(x+1) 
-3*4-3*x+3x=6*x+6*1
-12-3x+3x=6x+6
-6x=6+12
-6x=18
x=18/-6
x=-3

i) 2(-5x+3) + 7(3x-1)=0
2*(-5x)+2*3+7*3x+7*1=0
-10x+6+21x+7=0
-10x+21x=-7-6
11x=-13
x=-13/11

j) 5(4x+3) + 2(x+6) = 3(x+8)
5*4x+5*3+2*x+2*6=3*x+3*8
20x+15+2x+12=3x+24
20x+2x-3x=24-15-12
19x=-3
x=-3/19
Meilleure réponse !
2014-03-31T18:38:22+02:00
a) 4x + 3 = 3x - 5
4x - 3x = -3 - 5
x = -8

b) -2x + 7 = 3x - 13
- 2x - 3x = - 7 - 13
-5x = -20
x = 20/5
x = 4

c) -3x + 4 = 6x + 5
-3x -6x = -4 + 5
-9x = 1
x = -1/9
x = -0,11

d) 4 - 7x = -3x + 1
4 - 1 = 7x - 3x
3 = 4x
4x = 3
x = 3/4
x = 0,75

e) 3 (x - 8) = 4x + 5
3x - 24 = 4x + 5
3x - 4x = 24 + 5
-x = 29
x = -29

f) -4(2 + x) = 3x - 5
-8 - 4x = 3x - 5
-4x - 3x = 8 - 5
-7x = 3
x = -3/7
x = -0,43

g) 9(2 - 2x) = - (7x + 1)
18 - 18x = -7x - 1
-18x + 7x = -18 - 1
-11x = -19
x = 19/11
x = 1,72

h) -3 (4 + x) + 3x = 6(x + 1)
-12 - 3x + 3x = 6x + 6
-3x + 3 - 6x = +12 + 6
-6x = -18
x = -18/6
x = -3

i) 2(-5x + 3) + 7(3x - 1) = 0
-10x + 6 + 21x - 7 = 0
-10x + 21x = - 6 + 7
11x = 1
x = 1/11
x = 0,09

j) 5(4x + 3) + 2(x + 6) = 3(x + 8)
20x + 15 + 2x +12 = 3x + 24
20x + 2x - 3x = -15 - 12 + 24
22x - 3x = - 27 + 24
19x = - 3
x = -3/19
x = - 0,157